Efforts to Increase Student Activity in Online Learning Through Quiziz . Educational Game Media - Wahyuni, Sri (Universitas Sebelas Maret, 2020)
The study aims to determine the increased activity of learning in online learning through the media of educational Quiziz. This research is a class action study with subjects of grade IV at SDN 2 Gambiranom, as much as 9 people. The study implemented 2 cycles, each cycle 2 times the meeting. Each meeting is based on 4 stages, namely planning, implementation, observation and reflection. Based on the results of the study, at a cycle I gained an average student who was active 50% with low catagories. While in cycle II obtained average students active 83,5% with high catagori. So from cycle I and cycle II occurred an increase in the activity 33,5% students. Thus, research can be concluded that educational game media Quiziz can increase the activity of students in online learning at grade IV SDN 2 Gambiranom,on five theme.